EVEKTIFITAS MODEL PEMBELAJARAN KOOPERATIF TPS (THINK PAIR SHARE) BERBANTUAN MEDIA INTERAKTIF POP-UP BOOK DALAM PEMBELAJARAN IPAS TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV DI UPTD SD NEGERI PAILELANG - Betseba Y. Bayang; Nehemia Fanpada; Petrus Mau Tellu Dony (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The town of Unitita Bathsheba 22586026015. The effectiveness of the TPS (think pair share) cooperative learning model assisted by pop-up book interactive media in social studies learning on the learning outcomes of grade IV students at UPTD SD Negeri Pailelang. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Tribuana Kalabahi University. Supervisor I: Nehemia Fanpada, S.Pd. M.Pd and supervisor II: Petrus Mau. Three. Dony, S.Pd., M.Pd. This research is based on the low learning outcomes of science and science learning for grade IV students, because teachers have not used varied learning models and media. The purpose of this study is to determine the effectiveness of the TPS (Think Pair Share) Cooperative Learning Model with the Help of Pop Up Book Interactive Media in Social Science Learning in Grade IV at UPTD SD Negeri Pailelang. This study uses a quantitative research type pre-experiment method with a one-group approach (pre-test post-test) with a sample size of 30 students, the sampling technique is saturated sampling. Based on the results of the research conducted by the researcher through data collection techniques through tests with a one-group pretest-posttest research design. Before conducting the test, a material feasibility test and media feasibility were carried out through a material validity test of 88 and a validation of pop up book media of 84, a reliability test of 0.84, differentiating power and a test difficulty index. Furthermore, a prerequisite test for the normality test of 0.085 was carried out. After that, a test was carried out with a hypothesis test using the Paired Sample t-test, after which the data was analyzed using the help of SPSS 22 and got the results of thit – 18. 539 and ttab 1. 699 meaning that thit >ttab then H0 was rejected and H1 was accepted. From these results, it can be concluded that by using the think pair share cooperative learning model assisted by interactive media pop up books in learning IPAS on solar system materials, at UPTD SD Negeri Pailelang can be effective in student learning outcomes.